THE EFFECTIVENESS OF THE IMPLEMENTATION OF VIDEO YOUTUBE TO IMPROVE STUDENTS’ ABILITY IN WRITING PROCEDURE TEXT - Audhia, Hikmah; Atmowardoyo, Haryanto; Baa, Sultan (Universitas Negeri Makassar, 2022)
The purpose of this research is to find out the effectiveness of the implementation of video youtube to improve students' ability in writing procedure text. The method used in this research was pre-experiment with one group pretest-posttest. The population in this research were students of Class IX at SMP Negeri 8 Makassar for the 2022/2023 academic year. This research used a cluster random sampling technique. The sample was class IX.2, which consisted of 33 students. The instrument used in this research was pre-test and post-test. The results of this research, the mean score of students' pre-test and post-test increased (74.06 to 89.79). The standard deviation score for the pre-test (12.20) and post-test (11.28), showed that the standard deviation of the post-test was smaller than the standard deviation of the pre-test. The n-gain score was 0.59, with 58.57%. Then, the result of statistical hypothesis testing by using sample t-test found that (Sig < α (0.05)), Therefore, Ho was rejected and H1 was accepted, which means that the implementation of video is effective in improving students' ability in writing procedure text.